Promoting Critical Reading with Double-Entry Notes: A Pilot Study - Lindsey Ives; Taylor Joy Mitchell; Helena Hübl (Park University, 2020)
Recognizing a need to promote critical reading among students at our STEM university, the authors implemented an active reading strategy called double-entry notes across four general education writing and humanities courses. We hypothesized that the tool would help engage students in the critical reading strategies they tended to lack. The tool aimed to encourage students to think critically about assigned readings by analyzing texts, applying assigned readings to the world outside the text, synthesizing multiple texts, and the like. After assigning the tool, we assessed its effectiveness through a survey of students' perceptions and coded artifacts (N=182) for six markers of critical thinking. Results suggest that the tool succeeded in helping students to think critically about texts but that some markers of critical thinking were more consistent than others. Also, students' perceptions of the double-entry notes' benefits did not align with our findings based on analysis of their texts. Because results revealed critical engagement in reading, we plan to continue the study, adjusting the tool to address more specific critical thinking strategies.